Monte Zara (Monastir - SU). About some monetary discoveries (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
The article exposes a selection of the coins unearthed in the course of the excavations conducted by the Chair of Pre-Roman Archaeology of the University of Milan in the site of Monte Zara - Is Obias, at Monastir (SU). The operations took place during four excavation campaigns (2015-2018) and allowed the discovery of 8 coins referred from the end of the 4th century B.C. to the 2nd century B.C.
Keywords: Monte Zara; Monastir; coins; coins of Punic-Sardinia; Roman Republic Coinage; Sardus Pater coins